If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 12 = 7x + -52 Reorder the terms: 12 + 15x = 7x + -52 Reorder the terms: 12 + 15x = -52 + 7x Solving 12 + 15x = -52 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 12 + 15x + -7x = -52 + 7x + -7x Combine like terms: 15x + -7x = 8x 12 + 8x = -52 + 7x + -7x Combine like terms: 7x + -7x = 0 12 + 8x = -52 + 0 12 + 8x = -52 Add '-12' to each side of the equation. 12 + -12 + 8x = -52 + -12 Combine like terms: 12 + -12 = 0 0 + 8x = -52 + -12 8x = -52 + -12 Combine like terms: -52 + -12 = -64 8x = -64 Divide each side by '8'. x = -8 Simplifying x = -8
| 9*8+10= | | 5(w-4)-8w=4 | | d+d+d=9 | | 17+7=a+8 | | 9*8-10= | | 2x-6=6x-14 | | 1.8Q-4.7-1.6Q=-0.8Q-4.1 | | 2236000-17740r=3500000 | | 8x+3-10x=-2(x-2)+x | | 34+5x=99 | | 5(w-4)-8=14 | | 0.6x-10=104x-14 | | 5=x^2-441 | | x+16(x-1)=7(3+x) | | 3+m=29 | | (2w^2+2w)+(9w^2+4w+3)= | | 5(x-3)+2k=41 | | 27+5s=189 | | (2w^2+2w)+(9w^3+4w+3)= | | -10x-10+3x=18 | | 39x+2=158 | | -2(8+2x)=-28 | | 4+8x=126 | | y-20=-42 | | 5x=8-12x+6 | | 25x+15=90 | | -5-3x=10 | | 3y+5=41 | | 2x-9+3x=9-x | | 103-1x+2x=6x-7 | | 1y=6-4y | | 12+6x=84 |